The treatment of foundation embroidery from an islamic perspective - Muhamad Nasir, Iffatul Afnan; Mohd Subri, Irwan (Penerbit UiTM, 2022)
The trend of foundation embroidery treatment has been widespread and frenzy among Muslim women. Foundation embroidery is one of the most sophisticated facial treatments in Malaysia. With the overly and grossly obsessed attitude toward beautiful faces, most women are willing to spend hundreds of money to look gorgeous in front of society. The sophistication of technology nowadays, especially involving facial treatment and so on, requires a lot and depth research and explanation because this not only consists of the safety of our health but also relates to Islamic law, especially for Muslim women. Thus, the objective of this study is to investigate the procedures and classification of foundation embroidery treatment as it is one of the most popular facial treatments nowadays, especially in Malaysia. Apart from that, this research aims to evaluate the law governing this therapy from a halal perspective and the health risks associated with foundation embroidery. A qualitative research method was employed in which the process of getting high-quality information from literature is studied inductively and deductively. The findings of this study reveal that health organisations and Islamic law prohibit the treatment of foundation embroidery as it gives more harm and risks to the consumer even though the consumer’s intention is in a good way. The study of scientists and dermatologists also proves it.